(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
With Constitutional Law 1 of 2022, the constitutional lexicon was enriched with new locutions (“biodiversity,” “ecosystems,” “future generations”) that embody more than just a legal dimension. From the perspective of constitutional law, by hierarchizing environmental value, Article 9 Const. has placed it in a balancing condition with other fundamental public interests. From a constitutional policy perspective, the “new words” chart the path for a different form of progress, which law alone cannot fully reflect, based on the preeminent value of intergenerational solidarity and which requires, for its full realization, a transformation of social ethics.